Employee Performance Reviewed from Organizational Culture, Retention, Employee Rewards, And Work Stress - Dyah Ayu Prabandari; Sudarwati Sudarwati; Istiatin Istiatin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The purpose of this study is to examine and analyze employee performance in terms of organizational culture, retention, employee rewards, and work stress at the Karanganyar Pratama Tax Office. The population in this study were 101 civil servants at the Karanganyar Pratama Tax Office with a saturated sampling technique. The data collection method was through questionnaires. The data analysis technique used hypothesis testing, multiple linear regression, t-test, F-test, and R2 test with the help of SPSS for Windows Release 23. The results of this study can be concluded that organizational culture does not have a significant effect on employee performance at the Karanganyar Pratama Tax Office. Retention does not have a significant effect on employee performance at the Karanganyar Pratama Tax Office. Rewards have a positive and significant effect on employee performance at the Karanganyar Pratama Tax Office. Work stress has a positive and significant effect on employee performance at the Karanganyar Pratama Tax Office. The results of this study indicate that49.1% of employee performance onKaranganyar Pratama Tax Office can be explained by the variablesorganizational culture, retention, employee rewards, and work stress, the remaining 50.9% is explained byother variables.